Features of the Application of Digital Strategy and Customer Journey Mapping to Promote Organic Products (Economics and region, 2018)
The article considers and generalizes marketing tools for promotion of organic products on the market. The advantages of using digital strategy and customer journey, which help to increase the company's capabilities in the struggle for consumers, are substantiated. The main elements of these strategies are defined, which improve the promotion of organic products markets.
Keywords: marketing; marketing strategy; organic products; digital strategy; customer journey mapping